2019
DOI: 10.1186/s40621-019-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, attitudes and practices of vehicle submersion incidents: a pilot study

Abstract: Introduction Vehicle submersions account for up to 10% of all drownings in high-income countries. Reports indicate that occupants may be conscious and functional, but possibly making incorrect decisions for self-rescue leading to drowning. This study investigated current public knowledge, attitudes and practices regarding vehicle submersion incidents and to determine if individuals, who are aware of educational efforts regarding vehicle submersions, indicated better responses. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…While FMVSS 226 may reduce ejection injuries and fatalities, it does not address the issue of vehicle submersion and occupant drowning (McDonald et al, 2019). Drowning is a significant cause of vehicle-related fatalities, with some studies finding vehicle-related incidents accounting for a substantial portion of flood deaths (McDonald et al, 2019).…”
Section: The Drowning Dilemmamentioning
confidence: 99%
See 2 more Smart Citations
“…While FMVSS 226 may reduce ejection injuries and fatalities, it does not address the issue of vehicle submersion and occupant drowning (McDonald et al, 2019). Drowning is a significant cause of vehicle-related fatalities, with some studies finding vehicle-related incidents accounting for a substantial portion of flood deaths (McDonald et al, 2019).…”
Section: The Drowning Dilemmamentioning
confidence: 99%
“…The use of laminated glass in side windows can make escape or rescue from a submerged vehicle significantly more difficult, as the glass cannot be easily broken (McDonald et al, 2019). This raises the question -why has ejection mitigation been prioritized over drowning prevention in vehicle safety standards?…”
Section: The Drowning Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…First, public education on the dangers of vehicle submersion, the promotion of safe driving practices, and the instructions for a proper self-rescue protocol would be valuable [6]. However, a recent study indicated that public understanding regarding vehicle submersion accidents is low, and it was proposed that the simple awareness of the SWOC self-rescue protocol [e.g., SEATBELTS off, WINDOWS open or broken, OUT immediately, CHILDREN first (oldest to youngest)] could help decrease the high fatality rate [15].…”
Section: Mitigation Of Ror Vehicle Submersionsmentioning
confidence: 99%
“…Education is one of the most important things in a person's life (Mack et al, 2021). Because education is what determines and organizes the future and direction of one's life (Liu et al, 2019;McDonald et al, 2019). Although not everyone thinks so, education remains the most important human need (Giger, 2018).…”
Section: Introductionmentioning
confidence: 99%